Algoritma Pendeteksi Titik Ekstrim Pada Sinyal ECG Untuk Analisis Awal Gejala Aritmia - M.Jasa Afroni; Bambang Minto Basuki; affan Bachri (Universitas Islam Lamongan, 2020)
Checking a patient's heart health is often done by recording the heart's electrical signals in the form of an Electrocardiogram (ECG). To identifya heart condition, it is customary to look at several extreme maximum and minimum points on the ECG signal known as PQRST points. Theheight of the extreme points and the distance (interval) between the points can be used to detect symptoms of heart disease such as arrhythmias.This study uses a Matlab-based maximum and minimum extreme point detection algorithm to detect PQRST points and analyze the position ofthese points to detect arrhythmia symptoms. Based on the test results using data obtained from Physionet MIT-BIH and cardiac patients at SaifulAnwar Hospital Malang, detection of the PQRST point can be done quickly and accurately using this method. However, this method is onlyintended to assist medical personnel in reading ECG signal recordings, not to replace the role of medical personnel in carrying out the diagnosis